ETHNOLOGY'S HOT NOTION?: A Discussion Forum on How to Return to "Tradition" Today. Issue 1 (14th August 2020) - Isnart, Cyril; Testa, Alessandro
Abstract : After the publication of Hobsbawm and Ranger's groundbreaking The Invention of Tradition and ten years after Noyes' essay, Tradition: Three Traditions, what do we, as specialists of European cultures, have to say about "tradition"? This forum invites a selection of scholars coming from various thematic fields and countries to think about the concept of tradition, considered as one of our first conceptual tools and ethnographic objects of investigation. The authors reflexively discuss in which ways their research experiences challenge their own perceptions, understanding, and reframing of tradition. More than mapping new and allegedly new – or better "recycled" – ways in which social, ethnic, religious, or political groups use and manipulate traditions, the authors also address their perplexities with the notion of tradition. They thus add a specific layer of reflection, touching on temporality, methodology, and theoretical frames, to their practices of folklore and ethnology today.